Review on Potential Application of Saponin-Based Natural Surfactants for Green Chemical Enhanced Oil Recovery: Perspectives and Progresses - Adenutsi, C.D. (American Chemical Society, 2023)
Synthetic chemical surfactants deployed in the petroleum industry to improve oil recovery to meet growing global energy demand are described to have detrimental environmental impacts and are expensive. In recent times, the exploration of saponin-rich plants as a substitute for environmentally threatening synthetic surfactants has garnered significant interest from researchers. Saponin-based natural surfactants (SBNSs) are nontoxic, biodegradable, and possess desirable properties for use in the oil and gas industry. This paper reviews the potential application of saponin-based natural surfactants in enhanced oil recovery processes that coincide with the interests of the United Nationsâ Sustainable Development Goal 7 for Affordable and Clean Energy. We reviewed the mechanisms of saponin-based natural surfactants in enhanced oil recovery (EOR), surfactant adsorption, and the recent advances in utilizing saponin-based natural surfactants for EOR purposes. We also provided a comprehensive analysis of the impact of salinity and temperature on the performance of SBNSs. Moreover, the study also presented the economic feasibility and limitations of SBNSs for field enhanced oil recovery applications. We identified that a good number of SBNSs can withstand harsh reservoir conditions, optimize interfacial tension by as high as 95.82 (although not to ultralow levels), and alter rock wettability from hydrophobicity to hydrophilicity, thereby reducing the contact angle by 3.64 to 87.5. SBNSs also successfully yielded a high incremental oil recovery factor of up to 36 in the postsecondary recovery stage. The advent of techniques, such as alkali incorporation and nanotechnology, support the achievement of ultralow interfacial tension, mitigation of surfactant adsorption, and oil recovery improvement. Future studies can adopt the recommendations outlined in this study to minimize uncertainty in the utilization of SBNSs and enhance their design for âgreenâ chemical enhanced oil recovery applications. Â© 2023 American Chemical Society.